(untitled) (Experimental biology, 2015)
Studied the size of the main groups of soil microorganisms, the enzymatic activity of soil erosion and bioremediation of contaminated soil before and after the introduction of organic fertilizers in different doses on the oily soil. field studies suggest that the introduction of organic fertilizers can significantly accelerate the degradation of the oil in the oil-contaminated saline soils Kyzylorda region. The number of major groups of soil microorganisms increased by 2-3 orders of magnitude, and the enzymatic activity of the soil increased, as compared to the control.